Vestibular sensory dysfunction: neuroscience and psychosocial behaviour overview - Kreivinienė, Brigita (Social Welfare: Interdisciplinary Approach, 2016)
The objective of the submitted contribution is to describe one of the sensory dysfunction - the vestibular system. The vestibular system is crucial sensory system for other sensory systems such as tactile and proprioception, as well as having tight connection to the limbic system. Vestibular sensory system has significant role for further physical, emotional and psychosocial development. Descriptive method and case analysis are applied in literature based research methodology. These methods are most appropriate as far the vestibular dysfunctions not always are recognized in young age even though are seen as high psychoemotional reactions (psychosocial behavior). The vestibular dysfunctions in young age can be scarcely noticeable as far more often they tend to look like "just high emotional reactions" as crying, withdrawal, attachment to mother etc. which could be sensed as normal reaction of young child. Detailed vestibular sensory dysfunction analysis is presented, also explanation of the neurological processes, and predictions are made for the further possible interventions.
Keywords: vestibular dysfunction; neuroscience; psychosocial behavior